Вплив реформи місцевого оподаткування на формування доходів сільських бюджетів - Письменний, В. В.; Pysmennyi, V. (ЦНТУ, 2019)
Обґрунтовано необхідність впровадження власних податків і зборів як додаткового джерела доходів сільських бюджетів. Вироблено критерії, які їм відповідають в частині унікальної бази оподаткування, оподаткування об’єктів, прив’язаних до певної місцевості, забезпечення малого розходження податкового навантаження в різних територіях, уникнення високих витрат на податкове адміністрування. Охарактеризовано елементи оподаткування цих платежів та їх роль у формуванні фінансової бази органів влади на селі. Обоснована необходимость внедрения собственных налогов и сборов как дополнительного источника доходов сельских бюджетов. The purpose of the study is to substantiate the need to introduce a subsystem of own taxation in the countryside and to characterize taxes and fees, which should become an additional source of revenue of rural budgets. The criteria that are consistent with the specifics of introducing own taxes and fees by the authorities in the countryside have been developed. In particular, they relate to a unique tax base, taxation of objects tied to a certain area, ensuring a small difference in the tax burden within different territories, avoiding high costs for tax administration. The order of calculation and the mechanism of the fee payment for collection of biological resources of a forest fund, fees for the extraction of minerals for own use, fees for occupying the territory of the settlement, fees for the use of local symbols for commercial purposes, taxes on trade outside markets, fees for the placement of external advertising, fees for the arrangement of territories have been characterized. Their role in shaping the revenue base of rural budgets has been determined, which should be related to the ability of the government authorities in the village to solve vital tasks on their own and envisages the ability to provide with the necessary revenues without the involvement of external sources. The emphasis has been made on the fact that the subsystem of own taxation should open up opportunities for combining different forms and methods of taxation depending on the principles of fiscal adequacy, economic efficiency, social justice, administrative simplicity, stability, tax flexibility and others, which are acceptable to local governments. It has been established that own taxes and fees should become an additional source of revenue of rural budgets, evolving from the system of local taxation.
Влияние реформы местного налогообложения на формирование доходов сельских бюджетов
The Impact of the Reform of Local Taxation on Rural Budget Revenues
Keywords: доходи місцевих бюджетів; власні податки та збори; податкові надходження; система місцевого оподаткування; local budget revenues; own taxes and fee; tax revenues; local tax system